HRM practices in micro enterprises focusing on employees’ satisfaction and commitment - Hashim, Junaidah; Ismail, Yusof (2011)
This study examines the extent of informality of HRM practices among micro enterprises and their affect on employees’ satisfaction and commitment. It involved 857 employees working in micro enterprises in Kuala Lumpur. The results revealed that HRM practices in micro enterprises are formal, employees are satisfied and committed. Employees’ commitment variance is 68.0 percent explained by the predictors and it is significant. The results of the study are meaningful to the SME literature since not much research has been conducted in the area of human resource management of micro enterprises as compared to the research about small or large companies.